The influence of circulation weather patterns at different spatial scales on drought variability in the Iberian Peninsula - Russo, Ana C.; Gouveia, Célia M.; Trigo, Ricardo M.; Liberato, Margarida L. R.; DaCamara, Carlos C. (Frontiers in Environmental Science, 2015)
Europe has suffered several extreme weather events which were responsible for considerable ecological and economic losses in the last few decades. In Southern Europe, droughts are one of the most frequent extreme weather events, causing severe damages and various fatalities. The main goal of this study is to determine the role of Circulation Weather Types (CWT) on spatial and temporal variability of droughts by means the new multi-scalar Standardized Precipitation Evapotranspiration Index (SPEI). This study aims also to identify the main CWTs associated with winter and summer droughts over different regions of Iberian Peninsula. During the period between 1950 and 2012, the most frequent CWTs were found to be the Anticyclonic (A), Cyclonic (C), North (N) and Northeast (NE) types. The trend analysis for winter season shows a clear increase of frequency CWTs associated to dry events (A, East and Southeast) and a decrease of frequency of C and northern types while in summer a clear decrease of NE is observed. The spatial patterns of correlation between SPEI and CWT show large patterns of negative correlations with winter frequencies of A and eastern weather types, while the reverse occurs with C and western types. This feature is highlighted on a regional approach. The NE type presents negative correlations Central, Northwestern and Southwestern regions during winter and positive correlations in Eastern region during summer. In opposition, the West type presents positive correlations in all regions (except Eastern region) during winter and does not present significant correlations during summer. In general, the predominant CWT associated to winter or summer drought conditions differs greatly between regions. The winter droughts are associated mainly with high frequency of E types and low frequency of W types for all areas, while the summer drought in eastern sectors are linked with low frequency of C type, as well as the western regions are related with the N type.